Case report: the dissociated response and clinical benefit of primary leiomyosarcoma of the bone treated with penpulimab plus lenvatinib after failed multi-line therapy - Wang, Bin; Han, Yin; Liu, Jie; Zhang, Xinyao; Zhuo, Hongyu; Jiang, Yu; Deng, Yaotiao (Frontiers in Pharmacology, 2023)
Leiomyosarcoma occurring in the bone as primary tumor localization is extremely scarce with limited cases described in the literature, accounting for less than 0.7% of all primary bone malignancies. Once distant metastasis occurs , patients have limited treatments and often a somber prognosis, which underscores the need for innovative and effective treatment approaches. The emerging evidence suggests that antiangiogenic therapy could inhibit angiogenesis and normalize vascular permeability in the tumor microenvironment (TME), which, in turn, increase immune effector cell infiltration into tumors. Immunotherapy depends on the accumulation and activity of immune effector cells within the TME, and immune responses and vascular normalization seem to be reciprocally regulated. Immunotherapy combined with antiangiogenic therapy has recently made great progress in treatment of various types of tumors. However, the effectiveness of the combination treatment in metastatic leiomyosarcoma is undetermined. In this study, we presented a rare case of primary leiomyosarcoma of the bone (PLMSB) located in the trochanteric region of the femur, accompanied by multiple distant metastases. After the failure of multi-line therapies including AI regiment as the adjuvant chemotherapy, anlotinib as the first-line therapy, GT regiment as the second-line therapy, and eribulin as the third-line therapy, the patient received combinational therapy with penpulimab plus lenvatinib. The best efficacy for this regimen was partial response, with a progression-free survival of 8.4 months according to the iRECIST criteria. After a dissociated response was detected without severe toxicities, the patient received local radiotherapy and continued treatment on penpulimab plus lenvatinib, who eventually achieved long-term survival benefit with a total of over 60 months of overall survival with good quality of life and ongoing. As our previous retrospective study found that one third of advanced STS patients could still achieve clinical benefits from rechallenge with multi-targeted tyrosine kinase inhibitors (TKIs), after the failure of previous TKI therapy, This case not only proved the superior clinical activity of immunotherapy combined with antiangiogenic therapy but also showed the possibility of TKI rechallenge in metastatic 4 leiomyosarcoma.this case provided the potential clinical activity of immunotherapy combined with anti-angiogenic TKI rechallenge in metastatic leiomyosarcoma.